Calidad de prácticas preprofesionales y formación profesional en Pedagogía de las Ciencias Experimentales Matemáticas y Física de la UNACH, 2022 - Cazco Carrasco, Miriam Asucena (2022)
The present investigation entitled "Quality of pre-professional practices and professional training in Pedagogy of Experimental Mathematical and Physical Sciences of UNACH, 2022", proposed as its main objective to determine the level of quality of pre-professional practices of execution and the perception of contribution for training professionals. A survey used which contained 22 questions, distributed in two blocks: block 1 of the quality level of pre-professional practices and block 2 of perception of contribution for professional training. Being quantitative in nature, a non-experimental, field design chosen. transversal, whose scope was descriptive-purposeful, the sample used was 70 students. Concluding that the quality of pre-professional practices is regular since the majority of students plan pedagogical actions following formats extracted from the internet since there is no pre-established format at the career level, in addition, only 69% of students supervised by the academic tutor and the same percentage supervised by the tutor of the receiving entity, where the internship experience was beneficial and helped to expand the capacities of future teachers. Based on the problem and the information collected, a class plan format and an evaluation matrix are proposed in order to improve the quality of pre-professional practices.